Regional Security in the Middle East: Sectors, Variables, and Issue - Lutfie, Ratu Zahirah (RMPI-BRIN, 2024)
The contents in this book adopted a comprehensive approach to identifying and analyzing the dynamics of security in the Middle East. The contents are divided into three parts. The first part focuses on identifying threats operating within the political, economic, social, and environmental sectors. The second part seeks to investigate the impacts of various factors, such as geography, environment, available resources, and migration patterns. This section is deemed essential by the authors, as these factors significantly influence future security in the Middle East. Meanwhile, the third part provides an in-depth examination of the political economy, addressing topics such as the role and effectiveness of regional human rights organizations, the causes of religious radicalization, the use of religion to justify political conflicts, the role and strategies of regional non-state violent actors, and the dynamics surrounding the Arab Spring..